Hypolipidemic effect of lime (Citrus aurantifolia) fruit ethanol extract on total cholesterol levels in rats - Putri, Welya; Sovia, Evi; Y Ferriani, Sherly (ACTA Medical Health Sciences, 2025)
High cholesterol levels are a significant risk factor for cardiovascular disease. Statins are commonly used to reduce total cholesterol levels; however, long-term use can lead to adverse effects such as myalgia, an increased risk of type 2 diabetes, and liver damage. As a result, there is a growing need for research into natural medicines for cholesterol management. Lime(Citrus aurantifolia) is rich in flavonoids, which have been shown to reduce cholesterol by inhibiting the HMG-CoA reductase enzyme, a mechanism similar to that of statins. This study aimed to evaluate the effect of lime fruit ethanol extract on total cholesterol levels in male Wistar strain rats induced with a high-fat diet and PTU. This study was conducted as a laboratory experiment using a post-test control group design. Male Wistar rats were divided into six groups: a normal control group, a negative control group (high-fat diet + PTU), a positive control group (simvastatin), and three test groups (lime fruit ethanol extract 0.875, 1.75, and 3.5 g/kg BW). The high-fat diet and PTU were induced for 14 days, and total cholesterol levels were determined using the enzymatic colorimetric method (CHOD/PAP) at the end. The administration of lime fruit ethanol extract at a dose of 0.875 g/kgBW significantly reduced total cholesterol compared to the negative control group (p=0.013), with no significant difference from the normal group (p=0.965). However, higher doses of 1.75 and 3.5 g/kg BW caused mortality in the test groups. These findings suggest that lime fruit ethanol extract effectively reduces total cholesterol levels at a dose of 0.875 g/kg BW. Further research is needed to determine the optimal dose and toxicity profile of lime fruit ethanol extract forhyperlipidemia therapy. DOI : 10.35990/amhs.v3n3.p118-129 REFERENCES Siregar FA, Makmur T. Metabolisme lipid dalam tubuh. J Inov Kesehat Masy. 2020;1:60–6. Sovia E, Roslaeni R, Prakasa B, Putri AA, Ulhaq AD, Djajasasmita D, et al. Antihyperlipidemic effect of bitter melon extract (Momordica charantia L.) in Wistar rats. Indones J Clin Pharm. 2022;11:209–16. Oktavelia W, Kusuma SAF. Therapy for dyslipidemia: plant inhibitors of HMG-CoA reductase. Indones J Biol Pharm. 2022;2:159–70. Al-Zahrani J, Shubair MM, Al-Ghamdi S, Alrasheed AA, Alduraywish AA, Alreshidi FS, et al. The prevalence of hypercholesterolemia and associated risk factors in Al-Kharj population, Saudi Arabia: a cross-sectional survey. BMC Cardiovasc Disord. 2021;21:1–8. Puspaseruni K. Tatalaksana dislipidemia terkait penyakit kardiovaskular aterosklerosis (ASCVD): fokus pada penurunan LDL-c. CDK. 2021;48:395–401. Lestari WA, Utari DM. Dominant factors of hypercholesterolemia among pre-elderly in working area of Rangkapanjaya public health center in Depok. BKM J Community Med Public Health. 2017;33:267–72. Noubiap JJN, Nansseu JRN, Bigna JJR, Jingi AM, Kengne AP. Prevalence and incidence of dyslipidaemia among adults in Africa: a systematic review and meta-analysis protocol. BMJ Open. 2015;4:1–5. Tsao CW, Aday AW, Almarzooq ZI, Anderson CAM, Arora P, Avery CL, et al. Heart disease and stroke statistics - 2023 update: a report from the American Heart Association. Circulation. 2023;147:93–621. Aman AM, Soewondo P, Arsana PM, Zufry H, Rosandi R, Walewangko OC, et al. Panduan pengelolaan dislipidemia di Indonesia. PB PERKENI; 2021. Adam JMF. Dislipidemia. In: Buku Ajar Ilmu Penyakit Dalam. Vol VI. Jakarta: Interna Publishing; 2014. p. 2549–58. Prastiwi SS, Ferdiansyah F. Kandungan dan aktivitas farmakologi jeruk nipis (Citrus aurantifolia s.). Farmaka. 2017;15:1–8. Minami GS, Lumbantoruan EC, Puteri, Nuraini R, Harianto JC, Fahrurroji A. The potential of sweet orange (Citrus sinensis) in cardiovascular health: a literature review. J Kedokteran dan Kesehatan Indonesia. 2023;:82–94. Purnamasari AW, Isnawati M. Pengaruh pemberian jus pare (Momordica charantia L.) dan jus jeruk nipis (Citrus aurantifolia) terhadap kadar kolesterol total tikus Sprague Dawley hiperkolesterolemia. J Nutr College. 2014;3:894–902. Lin LY, Chuang CH, Chen HC, Yang KM. Lime (Citrus aurantifolia (Christm.) Swingle) essential oils: volatile compounds, antioxidant capacity, and hypolipidemic effect. Foods. 2019;8. Cyndi B, Andriane Y, MNur I. Pengaruh pemberian ekstrak etanol daun jeruk nipis (Citrus aurantifolia Swingle) terhadap penurunan kadar kolesterol total darah pada mencit model hiperkolesterolemia. Pros Pendidikan Dokter. 2016;2:911–7. Ardiani R. Efek antikolesterol ekstrak etanol daun Afrika (Vernonia amygdalina Del.) pada tikus. 2017;2:153–8. Sasmita, Djabir YY, Yustisia I. Efek pemberian dangke terhadap kadar kolesterol dan trigliserida darah tikus pemodelan hiperkolesterolemia dan hipertrigliseridemia. Maj Farmasi Farmakol. 2023;27:43–6. Penelitian A, Arfan M, Simatupang B, Sutysna H. Pengaruh minyak zaitun dan olahraga terhadap kadar trigliserida tikus Wistar diet tinggi lemak. 2020;1. Christianty FM, Holidah D, Fajrin FA, Salsabina MCA, Roni A. Profil lipid dan gambaran histopatologi aorta tikus hiperlipidemia dengan pemberian ekstrak kopi hijau. J Ilmu Kefarmasian Indones. 2020;18:21–7. Sovia E, Kristiana R, Nurdina S, Rachman H. Cinnamon (Cinnamomum burmanii) extract hepatoprotection activity against isoniazid-induced rat serum aspartate transaminase (AST) levels. Acta Med Health Sci. 2024;:109–15. Untari MK, Pramukantoro E. Aktivitas antihiperkolesterolemia ekstrak etanol daun Stevia rebaudiana Bertoni pada tikus putih jantan. J Syifa Sci Clin Res. 2020;2:11–20. Sinaga EM, Ambarwati NF, Aritonang B, Ritonga AH. Making antiseptic solid soap ethanol extract lemon peel (Citrus limon (L.) Burm. f.). J Multidisiplin Madani (MUDIMA). 2022;2:877–88. Awad K, Serban MC, Penson P, Mikhailidis DP, Toth PP, Jones SR, et al. Effects of morning vs evening statin administration on lipid profile: a systematic review and meta-analysis. J Clin Lipidol. 2017;11:972–85. McPherson RA, Pincus MR. Henry’s Clinical Diagnosis and Management by Laboratory Methods. 24th ed. 2021. Yurista SR, Ferdian RA, Sargowo D. Principles of the 3Rs and ARRIVE guidelines in animal research. J Kardiol Indones. 2016;37:156–63. Andari F, Rahayuni A. Pengaruh pemberian serbuk biji labu kuning (Cucurbita moschata) terhadap penurunan kolesterol total tikus Wistar hiperkolesterolemia. J Nutr College. 2014;3:506–16. Nuralifah, Wahyuni, Parawansah, Shintia UD. Uji aktivitas antihiperlipidemia ekstrak etanol daun Notika (Arcboldiodendron calosericeum Kobuski) terhadap kadar kolesterol total tikus jantan galur Wistar. J Syifa Sci Clin Res. 2020;2:1–10. Mutia S, Fauziah, Thomy Z. Pengaruh pemberian ekstrak etanol daun andong (Cordyline fruticosa (L.) A. Chev) terhadap kadar kolesterol total dan trigliserida darah tikus putih (Rattus norvegicus) hiperkolesterolemia. J Bioleuser. 2018;2:29–35. Aprilia CA, Ninditasari G, Walujo BRD. Hypolipidemic effect and antioxidant activity of tamarind leaves extract in hypercholesterol-fed rats. Indones J Cardiol. 2017;38:72–80. Rindiany C, Widjastuti T. Pengaruh pemberian mikrokapsul ekstrak buah mengkudu (Morinda citrifolia L.) sebagai feed additive terhadap kadar kolesterol dan trigliserida darah ayam Sentul. J Nutr Ternak Trop dan Ilmu Pakan. 2022;4:129–37. Ezeigwe OC, Ani ON, Okafor MC. Toxicological studies of Citrus aurantifolia fruit juice in Wistar rats. Asian J Biochem Genet Mol Biol. 2022;:38–47. Shchérazade OSF, Pétronille AZ, Joseph FKY, Georges A. Study of the analgesic effect of the aqueous extract of the leaves of Citrus aurantifolia (Rutaceae) in mice. GSC Biol Pharm Sci. 2021;14:207–14.